Settlement Characteristics of Crassostrea madrasensis in the Cochin ackwaters* - NAIR, N UNNIKRISHNAN; NAIR, N BALAKRISHNAN (Fishery Technology, 2017)
Settlement pattern of Crassostrea madrasensis (Preston) at five different habitats in and around Cochin Harbour is reported. The settlement pattern is found to be considerably influenced by the distribution of salinity at the various locations. Peak settlement occurred when. salinity ranged between 22.4% 0 to 33% 0.